Integrating Time Into Family Business Research: Using Random Coefficient Modeling to Examine Temporal Influences on Family Firm Ambidexterity. (March 2014) - Allison, Thomas H.; McKenny, Aaron Francis; Short, Jeremy Collin
Organizational ambidexterity refers to a firm's ability to pursue both exploitation and exploration orientations. Despite research that suggests ambidexterity is a critical phenomenon in family firms, few studies directly examine the role of ambidexterity over time in family business. This study examines how family firm ambidexterity changes over time as a result of temporal-, firm-, and industry-level factors. We find that family firm ambidexterity is stable over time, punctuated by dramatic changes. We also find that the level of innovation required to compete in an industry is a predictor of changes in exploration versus exploitation over time among family firms.